Adoption of Artificial Intelligence Tools for English Language Learning Among Saudi EFL University Students: The Moderating Role of Faculty - Alharbi, Jamilah Maflah (Journal of Ecohumanism, 2025)
Purpose: This study explores the adoption of AI tools by Saudi EFL (English as a Foreign Language) learners using an extended Technology Acceptance Model (TAM). The research integrates additional factors such as perceived knowledge, engagement, and motivation to understand their influence on Saudi EFL university students' acceptance of AI tools. Research Method: Employing a cross-sectional survey design, data were gathered from 472 EFL students at King Saud University using a simple random sampling technique. The data were analyzed using Structural Equation Modeling (SEM) via AMOS (Version 29) in two stages: the measurement model and the structural model. Findings: The measurement model confirmed the reliability and validity of the study's constructs. The structural model tested the hypothesized relationships, revealing that perceived knowledge, engagement, and motivation significantly affect the perceived usefulness (PU) and perceived ease of use (PEoU) of AI tools among Saudi EFL learners. Both PU and PEoU were found to significantly influence students' behavioral intention to adopt AI tools for language learning. However, no moderating effect was found for faculty in the relationship between students’ perception (PU and PeoU) and their intention to adopt IA tools. Collectively, these external variables explained 35% of the variance in PU, 43% in PEoU, 65% in the intention to adopt AI, and 36% in the actual adoption of AI tools. Significance: This research represents a pioneering effort within the Saudi educational context. By extending the TAM model to include perceived knowledge, engagement, and motivation, the study provides valuable insights into factors that influence the adoption of AI tools in English language learning. These findings can guide educators, universities, and language centers in developing strategies to enhance AI tool adoption, thereby making language learning more accessible and effective for students.